2019
DOI: 10.1186/s12885-018-5232-6
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal prehabilitation in colorectal cancer patients to improve functional capacity and reduce postoperative complications: the first international randomized controlled trial for multimodal prehabilitation

Abstract: BackgroundColorectal cancer (CRC) is the second most prevalent type of cancer in the world. Surgery is the only curative option. However, postoperative complications occur in up to 50% of patients and are associated with higher morbidity and mortality rates, lower health related quality of life (HRQoL) and increased expenditure in health care. The number and severity of complications are closely related to preoperative functional capacity, nutritional state, psychological state, and smoking behavior. Tradition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
185
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 250 publications
(191 citation statements)
references
References 53 publications
3
185
0
3
Order By: Relevance
“…Further research should therefore focus not only on further increasing postoperative survival rates in older patients but also on quality of life and improvement of postoperative physical functioning. Prehabilitation programs could play a role in achieving this goal [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Further research should therefore focus not only on further increasing postoperative survival rates in older patients but also on quality of life and improvement of postoperative physical functioning. Prehabilitation programs could play a role in achieving this goal [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…[258][259][260] At least, the idea of "prehab" does not seem to have any negative outcomes, and international randomised trials are ongoing. 261 Although promising evolvements have been made, the level of postoperative complications in the SCRCR has remained rather stable for the last two decades. Around 35 % of the patients are registered with some form of complication.…”
Section: Post-operative Complicationsmentioning
confidence: 99%
“…Interest continues to grow into preoperative exercise or 'prehabilitation' as a strategy to improve postoperative outcomes [1,2] by increasing physiological reserve in surgical patients [3]. A 2015 Delphi study of 19 consultant colorectal surgeons [4] reported a consensus that exercise programmes should form part of the preoperative care pathway; however, there was no agreement on whether it would be feasible to deliver such interventions within the routine UK care pathway where treatment is required to be initiated with 31 days of the decision to treat [5].…”
Section: Introductionmentioning
confidence: 99%